HIV knowledge and health seeking behavior in Zambézia Province, Mozambique - Audet, Carolyn M. (2012)
HIV prevalence rates in Zambézia Province were estimated at 12.6% in 2009. A number of educational campaigns have been aimed at improving HIV transmission and prevention knowledge among community members in an effort to reduce infection rates. These campaigns have also encouraged people to seek health care at clinical sites, instead of employing traditional healers to cure serious illness. The impact of these programs on the rural population has not been well documented. To assess the level of knowledge about HIV transmission and prevention and health-seeking behavior, we interviewed 349 people in 2009 using free response and multiple choice questionnaires. Over half reported first seeking treatment at a government health clinic; however the majority of participants had visited a traditional healer in the past. Knowledge regarding prevention and transmission of HIV was primarily limited to the sexual origins of infection and the protective advantages of condom use. Increased educational level and having learned about HIV from a community health worker were associated with higher HIV prevention and transmission knowledge. Traditional healers and community health care workers were both conduits of health information to our study participants. HIV education and use of clinical services may be facilitated by partnering more closely with these groups.